THE IMPORTANCE OF DEVELOPING METACOGNITIVE STRATEGIES IN TEACHING SPEAKING (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
this research aimed to find out the student ability in speaking at students t Junior High School 2 Panca Rijang and this study is the result of a report from a case study on the effect of metacognitive teaching on speaking ability of lowranking junior high school students, the metacognitive strategy influences students' speaking achievement, namely by conducting a pre-test in one group and the design of the post-test was conducted to support the findings in the results of learning speaking after training.